Sengketa Transaksi Digital dalam Jual Beli Online Perspektif Hukum Islam - Dela Aprilia; Nadya Quwwatun Rabbaniah; Shadiqah Tirza Tsamarah; Kurniati Kurniati (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
This study examines the characteristics of digital transaction disputes in online buying and selling and evaluates the mechanisms for resolving these disputes based on Islamic law principles. The rapid development of digital technology has significantly transformed commercial activities in Indonesia, yet it has also contributed to a sharp increase in consumer complaints, particularly in e-commerce transactions. Secondary data from Bank Indonesia and the Ministry of Trade indicate that more than 90% of consumer complaints from 2022 to 2025 originated from online transactions, demonstrating the vulnerability of digital consumers to misinformation, delivery issues, unilateral cancellations, fraud, and product mismatch. Using a qualitative method with a normative legal approach complemented by conceptual, statutory, and empirical analysis, this study investigates the legal framework governing digital transactions and compares it with the principles of fiqh muamalah. Findings reveal that most disputes arise from violations of fundamental Islamic contractual principles, including uncertainty (gharar), unclear object of contract (ma’qud ‘alaih), imbalance of information, and failure to uphold honesty and good faith. While positive law provides consumer protection through the Consumer Protection Law and the Electronic Information and Transactions Law, its implementation remains limited, particularly in resolving digital disputes. Islamic law, through principles of justice (‘adl), transparency, prevention of harm, and amicable settlement (shulh), offers a comprehensive foundation for fair and efficient dispute resolution. The study concludes that integrating these Islamic legal principles within modern Online Dispute Resolution (ODR) mechanisms can enhance legal certainty, consumer protection, and ethical standards in digital commerce.